Assimilation, relationship adjustment, and perceptions of English language education of Korean students in Iloilo City. - Revesencio, Freelon A.
The study sought to describe and evaluate the stages of assimilation that are currently experienced, the kind of adjustment in terms of relationship with people both in academic and non-academic setting, and perception of English Language education of Korean students. thirty respondents from TESDA- accredited Learning Centers in Iloilo City participated in the study, Questionnaires were utilized to examine and analyze the variables under investigation. Results showed that all the stages of assimilation have been experienced by the respondents especially the integration stage. The findings also showed that Koreans had difficulties in living in a new environment whih caused them additional social support systems with Filipinos that is limited only to their tutors. And lastly, all the Lnaguage Centers considered in the study were evaluated as satisfactory in both terms of the performance of and the lessons being offered by the tutors as well as the student services and facilities.